2011
DOI: 10.2527/jas.2010-2872
|View full text |Cite
|
Sign up to set email alerts
|

Genetic parameters of serum vitamin A and total cholesterol concentrations and the genetic relationships with carcass traits in an F1 cross between Japanese Black sires and Holstein dams

Abstract: Blood sample and carcass trait data were collected from 841 and 3,219 fattening animals of an F(1) cross between Japanese Black sires and Holstein dams, respectively. Data on serum vitamin A and total cholesterol concentrations containing 582 to 739 records at 4 stages of beef-fattening production were used to estimate variance components and heritabilities for the 2 traits, based on fattening periods: less than 13 mo of age (stage 1), 14 to 18 mo of age (stage 2), 19 to 21 mo of age (stage 3), and greater tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Other studies have also reported that the subcutaneous fat thickness in bovines is positively correlated with the serum VA level (Kato et al . ). Moreover, Nade et al .…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Other studies have also reported that the subcutaneous fat thickness in bovines is positively correlated with the serum VA level (Kato et al . ). Moreover, Nade et al .…”
Section: Discussionmentioning
confidence: 97%
“…; Kato et al . ). In the present study, we found that the expression levels of genes related to muscle development were decreased by VA.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Previously, it was used to measure physiological characteristics for selection programs designed to improve animal production traits (18). In the present study, 10 blood metabolites were analyzed to determine if any of these factors were correlated with the consumption of pure EA, TVA or CLA.…”
Section: Analysis Of Blood Metabolites a Metabolic Profile Test (Mpt)mentioning
confidence: 99%